Names of fish and bird of Turkism’s in Russian language - Turarova, G. K. (Journal of Oriental Studies, 2016)
In this article it is considered and analyzed the Turkish words, which are borrowed from Russian language by different reasons, I.e. Turkism’s in the meaning of fish and bird.